Using Future Internet Technologies to Strengthen Criminal Justice - Hollywood, John S. (RAND Corporation, 2015)
RAND conducted an expert panel on the criminal justice community's need to take advantage of (and mitigate threats from) emerging web technologies. This report outlines the technologies that were considered, the needs developed, and the overarching themes that arose during the panel proceedings.